2010
DOI: 10.1016/j.jaapos.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the burden of amblyopia treatment from the parent and child’s perspective

Abstract: Purpose-To evaluate the psychometric properties of the original Parent and new Child Amblyopia Treatment Index (ATI), questionnaires that assess the burden of amblyopia treatment in children and families, and to compare scores between children treated with atropine or patching.Methods-Parent ATI and Child ATI were administered to 233 children 7 to <13 years old and their parents as part of a randomized trial comparing patching and atropine for amblyopia treatment. For each ATI version, construct validity was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…The MOTAS (Monitored Occlusion Treatment of Amblyopia Study) group reported that only 30% of their trial participants achieved 100% amblyopic-deficit correction (same visual acuity in both eyes), with 57% achieving a visual acuity in the amblyopic eye of <0.1 logMAR of the fellow eye and 69% reached <0.2 logMAR of the fellow eye 9. Consequently, optimisation of patching treatment, by finding the most effective regimes, is likely to yield considerable cost benefits to health services, as well as being less onerous to patients and families 10 11…”
Section: Introductionmentioning
confidence: 99%
“…The MOTAS (Monitored Occlusion Treatment of Amblyopia Study) group reported that only 30% of their trial participants achieved 100% amblyopic-deficit correction (same visual acuity in both eyes), with 57% achieving a visual acuity in the amblyopic eye of <0.1 logMAR of the fellow eye and 69% reached <0.2 logMAR of the fellow eye 9. Consequently, optimisation of patching treatment, by finding the most effective regimes, is likely to yield considerable cost benefits to health services, as well as being less onerous to patients and families 10 11…”
Section: Introductionmentioning
confidence: 99%
“…It may be that Atropine occlusion, not being as obvious to the peer group, may have less psychological impact than patching therapy. Felius et al concluded that "Atropine treatment was found to have a less negative impact than patching" (Felius 2010). This finding is important in deciding how to offer and deliver occlusion treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5 Randomized clinical trials have used a parent-completed questionnaire, the Amblyopia Treatment Index, 6,7 to assess the effect of the treatment on the child’s quality of life. 8,9 …”
mentioning
confidence: 99%